Wastewater Treatment and Reuse Technologies - Jega Veeriah Jegatheesan (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This edited volume is a collection of 12 publications from esteemed research groups around the globe. The articles belong to the following broad categories: biological treatment process parameters, sludge management and disinfection, removal of trace organic contaminants, removal of heavy metals, and synthesis and fouling control of membranes for wastewater treatment.